1993
DOI: 10.1002/jcp.1041570322
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stretch on growth and collagen synthesis in cultured rat and lamb pulmonary arterial smooth muscle cells

Abstract: There are no studies of the effect of stretch in cultured pulmonary vascular smooth muscle, and some data suggest that a stretch-mediated increase in connective tissue synthesis in pulmonary arteries is mediated by the endothelium. To investigate whether stretch can serve as a growth stimulus in this smooth muscle, we studied two types of cultured pulmonary arterial smooth muscle cells (a multiply passaged clonal line of rat cells [PAC1], and early passage lamb cells [EPTC]). Cells were grown on a collagen-coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 43 publications
2
20
1
Order By: Relevance
“…Mechanical stretching of SMCs cultured on distensible substrata or entrapped in collagen gels has been shown to have profound effects on SMC phenotypic state, [99][100][101][102][103][104][105][106]101,[106][107][108][109]9,96,[110][111][112][113][114][115][116][117][118][119] growth factor release, 120 -122 proliferation, 100,123,124 and vascular tone, 125,126 leading several groups to investigate these mechanisms as a means of enhancing the development and maturation of tissue-engineered arteries. In particular, Kanda et al showed that adult bovine SMCbased collagen MEs that were cyclically loaded at 1 Hz with a strain amplitude of 10% for up to 4 weeks exhibited increases in contractile components such as myofilaments, dense bodies, and basement membranes, 106 indicating that cyclic stretching induces SMC reversion to a more contractile phenotype.…”
Section: Cyclic Stretching/distension Of Constructsmentioning
confidence: 99%
“…Mechanical stretching of SMCs cultured on distensible substrata or entrapped in collagen gels has been shown to have profound effects on SMC phenotypic state, [99][100][101][102][103][104][105][106]101,[106][107][108][109]9,96,[110][111][112][113][114][115][116][117][118][119] growth factor release, 120 -122 proliferation, 100,123,124 and vascular tone, 125,126 leading several groups to investigate these mechanisms as a means of enhancing the development and maturation of tissue-engineered arteries. In particular, Kanda et al showed that adult bovine SMCbased collagen MEs that were cyclically loaded at 1 Hz with a strain amplitude of 10% for up to 4 weeks exhibited increases in contractile components such as myofilaments, dense bodies, and basement membranes, 106 indicating that cyclic stretching induces SMC reversion to a more contractile phenotype.…”
Section: Cyclic Stretching/distension Of Constructsmentioning
confidence: 99%
“…43 In brief, medium was mixed with buffer containing 0.65 mol/L NaCl, 100 mmol/L Tris-Cl, pH 7.4, 4.7 mmol/L CaCl 2 , 1.25 mg/mL n-ethyl maleimide, and 50 g/mL BSA. Samples were split into 2 equal portions and highly specific collagenase (Sigma type VII, 10 U/mL) was added to 1 portion.…”
Section: Collagen Synthesis Assaymentioning
confidence: 99%
“…Endothelial cells are known to respond to shear stress and cardiac myocytes to strain with teleologically understandable alterations (Li et al, 1999a;Wung et al, 1999). As well, the response of cells of the kidney (Hirakata et al, 1997;Ingram et al, 1999) and lung (Kulik and Alvarado, 1993), to name but a few other organs, demonstrably respond to their mechanical environments. Indeed, as onecelled organisms are known to respond to pressure generated by the height of fluid in which they exist (Sukharev et al, 1997), it would seem logical that an ability to respond to the mechanical environment would be an adaptive evolutionary stress that might have affected the joining of cells into complex organisms during evolution.…”
Section: Introductionmentioning
confidence: 99%